Розгляд слідчим суддею клопотання про залучення експерта - Гловюк Ірина Василівна; Гловюк Ирина Васильевна; Glovyuk Iryna V. (My University, 2016)
The article is dedicated to the issue of consideration of the application of defense for involvement of expert. The lack of statements in art. 244 of CPC of Ukraine related to the parties’ participation, local facts in proof, the interpretation of inability of selfinvolvement of an expert were analyzed. Based on court practice it was proved that legal regulation of examination of appropriate applications by investigating judge has to be improved in such aspects as: the improvement of conditions for dismissal an application, subjects of dismissal, the notification of parties of criminal proceedings about the consideration of application, notification of investigator and prosecutor (in case when defense try to prove that the prosecution has failed to involve expert, or the questions posed before the expert involved by the defense would not enable a full and adequate opinion as to the issues whose clarification requires the expert examination, or there are reasonable grounds for believing that the expert involved by the defense will return or has returned an incomplete or incorrect opinion as a result of his lacking required expertise, being prejudiced or for other reasons).

Статья посвящена исследованию проблемных вопросов нормативной регламентации общих правил применения мер обеспечения уголовного производства. Указано, что в УПК нет общих правил относительно продления сроков, изменения и отмены мер обеспечения уголовного производства, кроме изменения мер пресечения. Предложено изложить ст. 132 УПК в уточненной редакции.

The article is devoted to the study of problematic issues of law regulation of the general rules of application of measures to ensure criminal proceedings. It was indicated that the CPC does not have general rules for extending the terms, changing and abolishing measures to ensure criminal proceedings, except for changing restrain measures. Proposition to clarify Art. 132 of the CPC was made.
Гловюк І. В. Розгляд слідчим суддею клопотання про залучення експерта / І. В. Гловюк // Eurasian Academic Research Journal. - 2016. - №2 (02). - С. 23-28.
Keywords: consideration; involvement of expert; investigating; court; prosecution; expertise; клопотання; залучення експерта; розслідування; суд; судовий розгляд; експертиза; ходатайство; привлечение эксперта; расследование; суд; судебное разбирательство; экспертиза